VALIDITAS TIGA VARIABEL DERMATOGLIFI ( GARIS SIMIAN, POLA HIPOTHENAR, SINUS ULNARIS ) UNTUK PENUNJANG DIAGNOSIS SINDROM DOWN PADA ANAK - , Murniati Rahayu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
BackgroundDermatoglyphics can be helpful to confirm a diagnosis, because it showtypicalpattern, shape, size and complexity.Diagnosis Down syndrome in infants by using clinical manifestation is difficult and often do not provide definitive results. Some experts suggest checking dermatoglyphics because of its good diagnostic value in this disorder. Objective To know validity of three variables dermatoglyphics (simian line, pattern of hypothenar, and ulnar loops) tosupport a diagnosis of Down syndrome. MethodWe conducteda cross sectional study in mentally retarded children at SLB from November through December 2010. The number of participantswere 103 children aged 5-18 years at SLB in Yogyakarta. The difference of dermatoglyphics between Down syndrome and non Down syndrome was analyzedby using bivariate analysis with a significant level of <0.05, while the diagnostic analysis we used 2 x 2 table diagnostic test. Results Three variables dermatoglyphics (simian line, pattern of hipothenar, ulnar loops) have a fairly good diagnostic value overall, specificity 95.6%, accuracy 81.6%, positive predictive value 86.4%, negative predictive value80.2%, positive likelihood ratio of 12.31, and negative likelihood ratio 0.47. But these variables dermatoglyphics have a value of sensitivity are quite low at 54.3%. ConclusionThree variables dermatoglyphics (simian line, pattern of hipothenar, ulnar loops) are quite valid to be used as supporting diagnosis of Down syndrome in children, but not suitable to be a screening tool in Down syndrome because of its low sensitivity.